Indications, benefits and risks of transoral thyroidectomy. Issue 4 (August 2019) - Zhang, Daqi; Park, Dawon; Sun, Hui; Anuwong, Angkoon; Tufano, Ralph; Kim, Hoon Yub; Dionigi, Gianlorenzo
Abstract : The advancement of minimally invasive surgery in the field of endocrine surgery over the last 2 decades has fostered the attempt of natural orifice transluminal endoscopic surgery (NOTES) for thyroidectomy and parathyroidectomy via oral incisions. This technically demanding surgery is currently being evaluated in a number of specialised centres. The procedure has gained popularity worldwide and is performed in more than 50 centres. By retrieving information from published or presented articles and direct personal communications, this study reports several issues to enable and optimise correct patient and surgeon candidacy, present the advantages and prevent novel complications under the standards of open thyroid surgery. Not all patients are eligible for the transoral approach. Transoral endoscopic and robotic procedures were described and critically analysed in this study.